Road to Net Zero. Strategic Pathways for Sustainability-Driven Business Transformation. - Zipse, Oliver; Hornegger, Joachim; Becker, Thomas; Beckmann, Markus; Bengsch, Michael; Feige, Irene; Schober, Markus (Springer, 2023)

Setting the Course for Net Zero: Translating Climate Science into Political and Corporate Targets - Beckmann, Markus; Zöttl, Gregor; Grimm, Veronika; Becker, Thomas; Schober, Markus; Zipse, Oliver (Springer International Publishing, 2023)
The Road to Net Zero starts from the Paris Agreement, which sets a global goal to limit global warming to well below 2 °C above pre-industrial levels, and an ambition to limit warming to 1.5 °C. The Agreement represents a turning point in the approach to tackling climate change, moving from a mitigation logic focused on reducing carbon emissions to an exit logic focused on full decarbonisation. The challenge is to translate the ambitious goals of the Paris Agreement into practical and achievable action plans that can be implemented at national and local levels. This will require a coordinated and joint effort by governments, businesses, and civil society to mobilise resources, build capacity, and put in place the necessary policies and regulations to support the transition to a low-carbon future. After discussing basic climate science foundations in Sect. 2.2 and the global climate policy ‘Road to Paris’, as well as the implications of the Paris Agreement in Sect. 2.3, national policy frameworks and governance mechanisms that can be implemented at the national level to meet the Nationally Determined Contributions (NDCs) are reviewed in Sect. 2.4. While the expert discussion between Prof. Grimm, Dr Becker, and Oliver Zipse in Sect. 2.5 is dedicated to the balancing act between technology openness and energy policy control mechanisms, Sect. 2.6 gives an outlook on how the goals of the Paris Agreement can be broken down to the company level. In this context, future research questions for the evaluation of legitimised measurement and target-setting frameworks for the private sector are discussed.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Carbon budget; Climate policy measures; Climate science; Paris Agreement; Science-based targets; Technology openness

Setting the Course for Net Zero. Translating Climate Science into Political and Corporate Targets. - Beckmann, Markus; Zöttl, Gregor; Grimm, Veronika; Becker, Thomas; Schober, Markus; Zipse, Oliver (Road to Net Zero. Strategic Pathways for Sustainability-Driven Business Transformation., 2023)

The Future of Corporate Disclosure: Non-financial KPIs, Sustainability and Integrated Reporting - Fischer, Thomas; Schober, Markus; Zipse, Oliver; Townend, Jonathan; Adolf, Jennifer (Road to Net Zero: Strategic Pathways for Sustainability-Driven Business Transformation, 2023)
The growing interest in a company’s sustainability strategy and performance means that solely providing financial information in corporate disclosures will no longer fulfil stakeholder needs in the future. Traditional financial reporting is primarily targeted at capital providers and therefore provides information on the company’s current and future financial performance. Today, a broader focus on non-financial, sustainability-related aspects is required to meet the information needs of other stakeholders, such as employees, customers, suppliers, government and society. Non-financial information is also increasingly important for investors to assess a firm’s risks and opportunities related to sustainability issues, such as climate change, and to understand how the firm is preparing itself for these future challenges. The transition of non-financial reporting-in particular, sustainability reporting-is evolving from voluntarily applied frameworks to mandatory regulatory requirements by standard-setting institutions. The aim is to provide higher transparency and comparability and to build the basis for linking the former separate financial and sustainability reports of a firm on a concise integrated report. A key challenge is the choice (and clear definition) of appropriate performance indicators to achieve comparability between firms. As a result, new rules and formats for corporate reports and for financial, as well as non-financial, disclosures are already appearing on the horizon and will sustainably change the future of corporate reporting. Adapting to these new regulations while balancing the interests of multiple stakeholders will become a continuous challenge for companies and will require them to engage in comprehensive, integrated thinking.
CRIS-Team Scopus Importer:2024-12-16
Keywords: The Future of Corporate Disclosure